Risk of hypertension in cancer patients treated with sorafenib: an updated systematic review and meta-analysis - Funakoshi, T; Latif, A; Galsky, M D (Journal of human hypertension, 2013)
Sorafenib, a multi-kinase inhibitor, has been reported to be associated with hypertension (HTN). However, the risk of severe HTN with sorafenib treatment has not been well described. We performed an up-to-date meta-analysis of high-grade HTN in cancer patients treated with sorafenib. Medline databases and the American Society of Clinical Oncology online database of meeting abstracts were searched up to August 2012 for relevant clinical trials. Eligible studies included phase II and III trials of sorafenib in patients with any type of cancer describing events of HTN according to the Common Terminology Criteria for Adverse Events. The summary incidence, relative risk (RR), and 95% confidence intervals (CIs) were calculated. The incidence of sorafenib-associated high-grade (grade 3–4) HTN was 6.0% (95% CI 4.7–7.3) in a total of 4722 patients from 55 trials of sorafenib as a single agent. Sorafenib-treated patients (4878 subjects from 13 randomized trials) had a significantly higher risk of high-grade HTN (RR 3.20 (95% CI 2.19–4.68)). Subgroup analysis revealed a significantly higher RR of high-grade HTN in patients receiving sorafenib as a single agent compared with patients receiving concomitant chemotherapy or immunotherapy ( P =0.0076). The incidence of high-grade HTN associated with sorafenib was significantly higher in patients with renal cell carcinoma (RCC) than those with non-RCC cancer ( P <0.0001) as well as patients treated with sorafenib for a longer duration than those treated for a shorter duration ( P =0.003). The use of sorafenib is associated with a significantly higher risk of high-grade HTN compared with control.